STRUCTUR AND STEREOTYPE IN SHORT STORY “SELAMAT PAGI, TUAN MENTERI” KARYA RADHAR PANCA DAHANA - Yusep Ahmadi F (JLER (Journal of Language Education Research), 2018)
This research is motivated by the importance of reading and deep story analysis in an effort to train analytical and aesthetic ability. This study aims to determine the structure and stereotypes in the short story "Good Morning, Mr. Minister" Work Radhar Panca Dahana. The method in this research is qualitative descriptive. The source of the data is taken from a collection of short stories from the story of Smoke Affairs of Radhar Panca Dahana. Data were analyzed by struturalism approach, that is analyzing and interpreting the structural elements (intrinsic) in the short story. The findings show that there are aspects of structures in the short story, theme, plot, figure, background, point of view, language style, and atmosphere. These aspects form a coherent unity so that the reader can understand the content of the story. In addition, stereotypes were also found. The stereotypes stem from the public's view of the main character, the public's negative view of the main character as a former official. It can be concluded that this stereotype is a social reality that the author discloses as a matter of social reflection.